2023
DOI: 10.3389/fpsyg.2023.1087729
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between parental involvement and psychological adjustment among Chinese children with autism spectrum disorder in the transition from kindergarten to primary school: A chain-mediating model

Abstract: IntroductionThis study examined the impact of parental involvement on the psychological adjustment of children with autism spectrum disorder (ASD), and the role of parenting self-efficacy and parenting stress in the transition from kindergarten to primary school.MethodsUsing the questionnaires, we collected data from 237 Chinese parents of children with ASD.ResultsMediation analyses showed that parental involvement partially promoted the psychological adjustment of children with ASD, which was reflected in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…According to Hoover-Dempsey et al's (2005) family involvement model [31], parenting stress is identified as an adverse psychological factor hindering parents' involvement in children's education. Other research has also indicated that the high level of stress associated with raising a child with severe behavioral challenges could lead to parents' low level of self-efficacy, which in turn, discourages them from actively engaging in children's educational activities [13,32]. Similarly, the parenting stress of raising a child with ASD has been identified as a factor associated with the negative long-term outcome of parental involvement, such as less parent-child interaction and low frequency of home-school communication [8,33].…”
Section: Mediation Effect Of Parenting Stress Between Family Ses and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hoover-Dempsey et al's (2005) family involvement model [31], parenting stress is identified as an adverse psychological factor hindering parents' involvement in children's education. Other research has also indicated that the high level of stress associated with raising a child with severe behavioral challenges could lead to parents' low level of self-efficacy, which in turn, discourages them from actively engaging in children's educational activities [13,32]. Similarly, the parenting stress of raising a child with ASD has been identified as a factor associated with the negative long-term outcome of parental involvement, such as less parent-child interaction and low frequency of home-school communication [8,33].…”
Section: Mediation Effect Of Parenting Stress Between Family Ses and ...mentioning
confidence: 99%
“…However, such a significant difference was not observed when children displayed severe behavioral problems. Semke et al (2010) found that reducing parenting stress for parents of children with severe disruptive behaviors alone failed to significantly increase their parental involvement [32]; this is due to the parents' low self-efficacy in their ability to help children achieve educational pursuits. In addition, mothers who experienced high stress levels from taking care of children with ASD rated their children's behavioral problems as more severe than those who experienced less parenting stress [44].…”
Section: Moderation Effect Of Asd Symptom Severitymentioning
confidence: 99%
“…According to Piotrowska et al (2017), this dimension consists of "paying attention, being receptive and open to new ways of interacting with children, actively contributing to discussions and tasks, completing homework tasks or asking questions" (p. 150). Studies have explored the relationship between parental involvement and positive children's outcomes, such as academic achievement (Boonk et al, 2018;Lara & Saracostti, 2019) and psychological adjustment (Hou et al, 2023). Therefore, parental involvement may constitute a protective factor for children's mental health in the Colombian context in which several risk factors are presented, including poverty, exposure to violence and war-related experiences, low parental educational levels, and negative parenting (Gómez-Restrepo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%